2011
DOI: 10.1073/pnas.1104834108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human astrovirus capsid spike

Abstract: Astroviruses are single-stranded, plus-sense RNA viruses that infect both mammals and birds, causing gastroenteritis and other extraintestinal diseases. Clinical studies have established astroviruses as the second leading cause of viral diarrhea in young children. Here we report the crystal structure of the human astrovirus dimeric surface spike determined to 1.8-Å resolution. The overall structure of each spike/projection domain has a unique three-layered β-sandwiches fold, with a core, six-stranded β-barrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 40 publications
5
119
0
Order By: Relevance
“…The HVR of AstV is believed to form the capsid spike (Dong et al, 2011) and to control binding to cell receptors as neutralising epitopes have been mapped inside this capsid portion. This region is subjected to impressive diversification across type-1 to -8 HAstVs, with the aa identity ranging from 44% to 69% (Sanchez-Fauquier et al, 1994;Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HVR of AstV is believed to form the capsid spike (Dong et al, 2011) and to control binding to cell receptors as neutralising epitopes have been mapped inside this capsid portion. This region is subjected to impressive diversification across type-1 to -8 HAstVs, with the aa identity ranging from 44% to 69% (Sanchez-Fauquier et al, 1994;Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The mature infectious virion contains three predominant protein species derived from the N-terminal domain and from the HVR after intra-and extra-cellular processing (Bass and Qiu, 2000;Sanchez-Fauquier et al, 1994). Mapping of neutralising monoclonal antibodies (Sanchez-Fauquier et al, 1994) and structural analysis have revealed that AstV capsid spike is formed by dimerisation of a polypeptide spanning the HVR and a putative binding receptor site with affinity for polysaccharide molecules has been predicted in the spike structure (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The capsid is a multidomain protein with a conserved N-terminal region and a highly variable C-terminal region (18)(19)(20)(21)(22). The conserved N-terminal region, comprising the basic, S, and P1 domains, encompasses the viral genome and forms the shell of the capsid (20,23). The highly variable C-terminal region comprises the spike (also called the P2 domain) and acidic domains (23).…”
mentioning
confidence: 99%
“…Astrovirus has been shown to increase epithelial cell permeability upon infection of Caco-2 cells in vitro, possibly due to a reduction in actin fibers [30], reduction of occludin from the junctional complex [30], and redistribution of e-cadherin 24 h post-infection (hpi; Figure 2). sulfate partially blocked HAstV-8 infectivity of Caco-2 cells [66]. However, pretreatment of Caco-2 cells with chondroitinase and heparinase did not significantly reduce HAstV-1 infection in the same cells [63], suggesting that there may be strain-and/or genotype-specific differences.…”
Section: Cell Culture and Animal Modelsmentioning
confidence: 75%
“…Crystallization of the human HAstV-8 and turkey astrovirus type 2 (TAstV-2) capsid and spike proteins [62][63][64][65][66] showed conserved polysaccharide binding motifs [65]. The addition of heparin, heparin sulfate, or dextran sulfate Viruses 2017, 9, 22 4 of 10 partially blocked HAstV-8 infectivity of Caco-2 cells [66]. However, pretreatment of Caco-2 cells with chondroitinase and heparinase did not significantly reduce HAstV-1 infection in the same cells [63], suggesting that there may be strain-and/or genotype-specific differences.…”
Section: Cell Culture and Animal Modelsmentioning
confidence: 99%